Endovascular treatment of multiple intracranial aneurysms in patients with subarachnoid hemorrhage: one or multiple sessions? - Zhang, Guangjian; Zhang, Weiwei; Chang, Hanxiao; Shen, Yuqi; Ma, Chencheng; Mao, Lei; Li, Zheng; Lu, Hua (Frontiers in Neurology, 2023)
Objective: This study aimed to compare safety and efficacy of single- and multiple-stage endovascular treatment in aneurysmal subarachnoid hemorrhage patients with multiple intracranial aneurysms. Methods: We retrospectively analyzed the clinical and imaging data of 61 patients who harbored multiple aneurysms and presented to our institution with aneurysmal subarachnoid hemorrhage. Patients were grouped according to endovascular treatment strategy: one-stage or multiple-stage. Result: The 61 study patients harbored 136 aneurysms. One aneurysm in each patient had ruptured. In the one-stage treatment group, all 66 aneurysms were treated in one session in 31 patients. Mean follow-up was 25.8 months (range, 12–47). At last-follow-up, modified Rankin scale was ≤2 in 27 patients. Ten complications occurred (cerebral vasospasm, 6 patients; cerebral hemorrhage, 2; and thromboembolism, 2). In the multiple-stage treatment group, only the ruptured aneurysm (30 in total) was treated at the time of presentation and the remaining aneurysms (40 in total) were treated later. Mean follow-up was 26.3 months (range, 7–49). At last follow-up, modified Rankin scale score was ≤2 in 28 patients. Five complications occurred (cerebral vasospasm, 4 patients; and subarachnoid hemorrhage, 1 patient). During the follow-up period, there was one recurrence of aneurysm with subarachnoid hemorrhage in the one-staged treatment group and four recurrences in the staged treatment group. Conclusion: Both single- and multiple-stage endovascular treatment is safe and effective in aneurysmal subarachnoid hemorrhage patients who harbor multiple aneurysms. However, multiple-stage treatment is associated with a lower rate of hemorrhagic and ischemic complications.